Giant cystic pheochromocytoma masquerading as acute coronary syndrome and transient left ventricular dysfunction: a case report - P. B., Sryma; N. C., Mary Grace; A. K., Abdul Siyad; Ahamed, Ijas (International Journal of Advances in Medicine, 2018)
Objective of present study to present an atypical manifestation of pheochromocytoma and to illustrate the difficulty in managing an acute coronary syndrome and left ventricular dysfunction during a hypertensive crisis attributable to pheochromocytoma. We present the clinical history, physical findings, lab results and imaging studies of a 62year old man with acute coronary syndrome later found to have an adrenal mass. A 62-year-old man was suspected of having myocardial ischemia on the basis of symptoms of paroxysmal chest discomfort, diaphoresis, ST-segment elevation on an electrocardiogram, and elevated levels of cardiac enzymes. Coronary CT angiography was normal. Echocardiography revealed substantial ballooning of the apical, anterior, and inferior cardiac walls, consistent with catecholamine induced cardiomyopathy. He had a history of labile hypertension, headache, diaphoresis and palpitations of 4 years’ duration. A right adrenal mass detected on Magnetic resonance imaging and increased plasma catecholamine levels were consistent with a pheochromocytoma. Treatment with prazosin and labetalol was initiated, and he underwent a right adrenalectomy, which confirmed thepheochromocytoma. Pheochromocytomas must be considered in the setting of acute coronary syndrome especially with presence of labile blood pressure. Inadvertent fibrinolysis can be avoided with proper clinical suspicion and timely coronary imaging.